2021
DOI: 10.3390/nu13030764
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Decaffeinated Green Tea Extract on Fat Oxidation, Body Composition and Cardio-Metabolic Health in Overweight, Recreationally Active Individuals

Abstract: This study investigated the effect of decaffeinated green tea extract (dGTE), with or without antioxidant nutrients, on fat oxidation, body composition and cardio-metabolic health measures in overweight individuals engaged in regular exercise. Twenty-seven participants (20 females, 7 males; body mass: 77.5 ± 10.5 kg; body mass index: 27.4 ± 3.0 kg·m2; peak oxygen uptake (O2peak): 30.2 ± 5.8 mL·kg−1·min−1) were randomly assigned, in a double-blinded manner, either: dGTE (400 mg·d−1 (−)-epigallocatechin−3-gallat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 89 publications
1
16
0
1
Order By: Relevance
“…In a study by Venables et al [33], a 13% increase in the Matsuda measured insulin sensitivity was observed in response to acute ingestion of green tea extract in healthy males compared to the placebo. Although the exact mechanism for the observed effects of green tea is not yet known, it is hypothesised that green tea acts via glucose transporters in tissues such as skeletal muscle, thus requiring less insulin to clear a given amount of glucose [34]. Similarly, in the TOAST study, an 8.3% higher insulin sensitivity in the 4 g/250 mL kawakawa group compared to control, demonstrating a possible role of kawakawa in regulating pathways related to insulin sensitivity.…”
Section: Discussionmentioning
confidence: 98%
“…In a study by Venables et al [33], a 13% increase in the Matsuda measured insulin sensitivity was observed in response to acute ingestion of green tea extract in healthy males compared to the placebo. Although the exact mechanism for the observed effects of green tea is not yet known, it is hypothesised that green tea acts via glucose transporters in tissues such as skeletal muscle, thus requiring less insulin to clear a given amount of glucose [34]. Similarly, in the TOAST study, an 8.3% higher insulin sensitivity in the 4 g/250 mL kawakawa group compared to control, demonstrating a possible role of kawakawa in regulating pathways related to insulin sensitivity.…”
Section: Discussionmentioning
confidence: 98%
“…Throughout both GXT protocols, continuous breath-to-breath respiratory assessment (MetaLyzer 3B, Cortex Biophysik, Leipzig, Germany) and telemetric heart rate monitoring (Polar Electro Ltd., Kempele, Finland) were captured. O 2max was estimated using the highest 15 breath rolling average oxygen consumption, with maximal individual effort determined through previously referenced criteria [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…Exercise activity and dietary monitoring were undertaken in a similar manner to that previously reported by our group [ 36 , 40 ]. Prior to, and across the full 16-day intervention, participants completed a standardized daily activity log to account for habitual exercise patterns based on session type, mean session heart rate, exercise duration and session perceived exertion (sRPE).…”
Section: Methodsmentioning
confidence: 99%
“…Polyphenols of green tea They increase maximal fat oxidation and shifts the point where fat is no longer oxidized to higher intensity levels [115,116] Anthocyanins from Prunus cerasus L.…”
Section: Modifying Factor Effect Referencesmentioning
confidence: 99%
“…The influence of some polyphenols has been described. For example, decaffeinated green tea extract has been reported to dramatically increase (+45%) MFO and shift the point where lipids are no longer oxidized (termed LIPOX zero or FATmin) toward intensities higher than 22.5% [115]. This effect reported during exercise involving the legs is no longer found during arm cycle exercise [116].…”
Section: Feeding and Dietary Habitsmentioning
confidence: 99%